2022
DOI: 10.1111/jvim.16427
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic characteristics of trained and untrained standardbred racehorses

Abstract: Background: Long-term exercise induces cardiac remodeling that potentially influences the electrical properties of the heart. Hypothesis/objectives: We assessed whether training alters cardiac conduction in Standardbred racehorses. Animals: Two hundred one trained and 52 untrained Standardbred horses. Methods: Cross-sectional study. Resting ECG recordings were analyzed to assess heart rate (HR) along with standard ECG parameters and for identification of atrial and ventricular arrhythmias. An electrophysiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…We found that non-active horses had significantly lower Pmax and Pd in comparison with horses that were racing. Another study, which recorded ECG parameters in a single lead (Lead II), has also identified a significant increase in P wave duration in trained versus untrained SB horses [ 47 ]. Contradictory results have been reported in the few studies investigating P wave indices in human athletes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that non-active horses had significantly lower Pmax and Pd in comparison with horses that were racing. Another study, which recorded ECG parameters in a single lead (Lead II), has also identified a significant increase in P wave duration in trained versus untrained SB horses [ 47 ]. Contradictory results have been reported in the few studies investigating P wave indices in human athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Resting HR in the horses in this study ranged from 32 to 40 bpm during the ECG data collection period and no associations were identified with P wave duration or dispersion. Recently, Nissen et al reported that trained SB horses had lower resting heart rates and increased frequency of 2nd-degree AV block compared with untrained horses [ 47 ]. In contrast, we found a slightly lower HR in non-active horses compared with those in race training, although HR in both groups was higher than those reported by Nissen et al In that study, ECG was monitored for 2 h whilst horses stood quietly in their stable.…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown if second-degree AV block with progressive prolongation of the PR interval also occurs in the AV node as in humans. We recently reported His signals from a case with second-degree AV block where the PR interval varied towards blocking but the His signals were present in the blocked beats, suggestive of infra-Hisian blocks [ 2 ]. This is an interesting observation, but more studies are needed to clarify this.…”
Section: Discussionmentioning
confidence: 99%
“…However, in horses with multiple AV blocks, echocardiography could add information about anatomical changes in this region. Though still being a rare procedure and not yet clinically available in horses, intra-cardiac 3D mapping and His bundle recordings could provide information on the electrical conduction in the AV nodal region as well [ 2 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation